DIRECTIONS FOR ASSESSING ATMOSPHERIC POLLUTION AND ENSURING SUSTAINABILITY IN UZBEKISTAN (Marketing Journal, 2025)
This study analyzes the impact of population growth, environmental education, and consumption patterns on air pollution levels in Uzbekistan. An econometric model was developed using panel data from 2010 to 2023, incorporating variables such as population size, environmental education, packaging consumption, and energy use. 585 Findings indicate that population growth and packaging consumption significantly increase pollutant emissions, while improving environmental education helps reduce pollution. Strategies focused on enhancing environmental awareness, reducing packaging waste, and promoting sustainable consumption are essential for reducing air pollution.
Keywords: air pollution; environmental education; packaging waste; sustainable development; Uzbekistan